The diffusion of environmental policy innovations: A contribution to the globalisation of environment policy - Kristine Kern; Helge Jörgens; Martin Jänicke (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
The subject of this paper is the importance of the diffusion of environmental innovations between countries for the global development of environmental policy. Empirical observation has shown that national environmental initiatives are often rapidly adopted by other countries; thus, these initiatives spread internationally. The conditions for and restrictions on the international diffusion of environmental innovations are examined on the basis of five case studies: environmental agencies and ministries, ecolabels, national environmental plans, CO2/energy taxes, and soil protection legislation. The key determinants of policy diffusion include (1) national factors (capacities for action in environmental policy, the demand for problem solutions), (2) the dynamics of the international system (the significance of front-runner countries for global policy diffusion, international organisations, transnational networks), and (3) aspects of the specific policy innovation (characteristics of policy innovation, availability of appropriate policy models, etc.). – – Thema dieses Beitrags ist die Diffusion umweltpolitischer Innovationen zwischen Nationalstaaten in ihrer Bedeutung für die globale Entwicklung von Umweltpolitik. Dabei geht es um die empirische Beobachtung, dass nationale Umweltinitiativen vielfach mit hoher Geschwindigkeit von anderen Ländern übernommen werden und sich auf diese Weise international ausbreiten. Anhand von fünf Fallstudien (Umweltämter und - ministerien, Umweltzeichen, nationale Umweltpläne bzw. Nachhaltigkeitsstrategien, CO2-/Energiesteuern, Bodenschutzgesetze) werden Erfolgsbedingungen und Restriktionen der internationalen Ausbreitung umweltpolitischer Innovationen untersucht. Zu den zentralen Determinanten der Politikdiffusion zählen: (1) nationalstaatliche Faktoren (umweltpolitische Handlungskapazitäten, Nachfrage nach Problemlösungen), (2) die Dynamik des internationalen Systems (Bedeutung von Vorreiterländern für die globale Politikdiffusion, internationale Organisationen, transnationale Netzwerke) sowie (3) Aspekte, die die Politikinnovation selbst betreffen (Charakteristika der Politikinnovation, Verfügbarkeit von geeigneten Politikmodellen etc.).
Keywords: 300; Internationale Umweltpolitik; Innovationsdiffusion; Welt